Effects of soil properties on the Cd threshold in typical paddy soils using BCR sequential extraction. Issue 8 (17th November 2019) - Chen, Qi; Peng, Peiqin; Hou, Hongbo; Ding, Xianqing; Long, Jian; Li, Xinyang; Liao, Bohan
Abstract: Soil quality standards used for agricultural land do not fully consider the effect of soil properties on cadmium (Cd) uptake by crops. A pot experiment with six types of soil derived from two typical soil parent materials was conducted to determine the effect of soil properties on the soil Cd fractions and Cd concentration in rice grain. The results of soil Cd fractions obtained by the Community Bureau of Reference sequential extraction revealed significant differences among soil types. Redundancy analysis showed that soil pH was the most influential factor affecting soil Cd fractions for red paddy soil, but soil pH, soil organic matter, and clay content were significant for purple paddy soil. Stepwise multiple linear regression analysis showed that soil clay and soil organic matter were the two most significant variables contributing to soil Cd threshold, explaining 97.8% of the variance. These results suggest that soil clay and organic matter contents should be considered when evaluating the risk of Cd in paddy soil.